DISTINGUISHING MEDIATED PERFORMANCE OF A CRIMINAL OFFENSE AND COMPLICATION IN A CRIMINAL OFFENSE - Omelchuk, Oleh; Zakharchuk, Viktor (Socio-economic relations in the digital society, 2023)
The purpose of the article is to distinguish between the indirect execution of a criminal offense and complicity in a criminal offense. This is due to the fact that in judicial practice there are quite a lot of cases when the objective side of a criminal offense is committed by several persons, but only one of them (the indirect executor) acts culpably, and other persons are misled about the true nature of their actions. It is also common for criminals to use persons who have not reached the age of criminal responsibility for the indirect execution of a criminal offense, especially when committing self-interested criminal offenses against property. The concept of such mediated performance was studied, its system was defined, and typical methods of its execution were characterized. The judicial practice of qualifying the indirect execution of a criminal offense by using persons who are not the subjects of a criminal offense, the use of persons who have the characteristics of a common subject of a criminal offense, but act innocently, or who act under the influence of irresistible physical or mental coercion, has been analyzed. The common and distinguishing features of the indirect execution of a criminal offense and complicity in it are given, and the main criteria that must be taken into account for making such a distinction are established. It is established that the indirect execution of a criminal offense will be provided that the objective side of the criminal offense is not executed by the guilty person either in whole or in part. After all, if a person performs at least a certain part of the objective side, then he acts as an executor (co-executor) of the act, and not as an indirect executor of it.